2013
DOI: 10.1111/febs.12577
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of survivin by AKT and hypoxia‐inducible factor 1α contributes to cisplatin resistance in gastric cancer

Abstract: This study investigated the contribution of survivin and its upstream regulators, AKT and hypoxia-inducible factor 1a , to the resistance of gastric cancer cells to cisplatin (CDDP). We found that over-expression of survivin increased the resistance of SGC7901 and BGC823 gastric cancer cells to CDDP. Its over-expression abrogated CDDP-induced inhibition of cell proliferation and CDDP-induced cell apoptosis. In contrast, down-regulation of survivin expression using small hairpin RNA (shRNA) vectors and the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 45 publications
4
69
0
Order By: Relevance
“…Therefore, a high level of CD44v6 expression may also contribute to the aggressive phenotype. In addition, the upregulation of Survivin by HIF-1α and PTEN contributed to cisplatin (CDDP) resistance, indicating that inhibition of these pathways may be a potential strategy for overcoming CDDP resistance in the treatment of gastric cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a high level of CD44v6 expression may also contribute to the aggressive phenotype. In addition, the upregulation of Survivin by HIF-1α and PTEN contributed to cisplatin (CDDP) resistance, indicating that inhibition of these pathways may be a potential strategy for overcoming CDDP resistance in the treatment of gastric cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Genistein exhibited a similar effect in the present study, in which HIF-1α-mediated survivin expression under hypoxic conditions and HIF-1α inhibition by genistein in HUVECs led to reduced rather than completely diminished survivin expression, even in the presence of 200 μM of genistein, implying that hypoxiainduced survivin expression can be initiated through other molecular pathways besides HIF-1α. To the best of our knowledge, this is the first study that shows survivin expression can be stimulated by hypoxia and CoCl2-induced HIF-1α accumulation in HUVECs in a time-dependent manner, although other studies have found hypoxia up-regulates survivin expression in cancer cell lines [45].…”
Section: Discussionmentioning
confidence: 76%
“…Unfortunately, despite a wide variety of approaches, human gastric cancer remains a major challenge with fewer effective targeted therapies than other cancers. Recently, it was reported that YM155 promotes cisplatin-induced apoptosis in gastric cancer (22). Our research focused on the inhibitory effect of YM155 alone on gastric cancer.…”
Section: Discussionmentioning
confidence: 99%